2009
DOI: 10.1007/s10528-009-9259-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Stability of Progeny from an Artificial Allotetraploid Carp Using Sperm from Five Fish Species

Abstract: Microsatellite markers and D-loop sequences of mtDNA from a female allotetraploid parent carp and her progenies of generations 1 and 2 induced by sperm of five distant fish species were analyzed. Eleven microsatellite markers were used to identify 48 alleles from the allotetraploid female. The same number of alleles (48) appeared in the first and second generations of the gynogenetic offspring, regardless of the source of the sperm used as an activator. The mtDNA D-loop analysis was performed on the female tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…When the eggs from the female tetraploids were fertilized by active or inactive sperm, all‐female, tetraploid progenies were produced. Analysis of microsatellite marker inheritance demonstrated that the tetraploid females were propagating via natural gynogenesis (Ye et al , , ).…”
Section: Introductionmentioning
confidence: 99%
“…When the eggs from the female tetraploids were fertilized by active or inactive sperm, all‐female, tetraploid progenies were produced. Analysis of microsatellite marker inheritance demonstrated that the tetraploid females were propagating via natural gynogenesis (Ye et al , , ).…”
Section: Introductionmentioning
confidence: 99%